Moral Education Value in Ahmad Fuadi’s Novel Rantau Satu Muara - Susanti, D (KnE Social Sciences, 2018)
This study analyzes the moral education Value in the novel Rantau Sastu Muara written by A. Fuadi. The purpose of this study is to find out the moral values found in the novel which are depicted in the characterization of the characters. This study is also done with objective to reveal the intrinsic elements as the supporting elements in analyzing the moral values or lessons. The results of this study show that there are six moral values which can be taken from the novel: Religious, Hard Work, Love Country, Communicative/friendly, Love Reading, Responsibility. The theory used in this study is proposed by Lickhona (2012) and the method used in analyzing the problems is proposed by Moleong (2009). The findings of this study are hoped to be the reference of individuals to have good morality in life. Keywords: moral, education, value, love